Basic Level Swimming Coach Training to Increase Knowledge of Coaching Beginner Swimmers - Wahyu Hidayat, Zakaria; Harja Nenggar, Aditya; Hamid, Faisol (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
The presence of a coach in a swimming club or association is very important in the success of a swimming athlete. For this reason, coaches must be equipped with knowledge about the basics of training beginner swimmers, a coach must also have a clear voice, a good attitude and an authoritative appearance. The reality in the field is often different, even though trainers already have the criteria above, it turns out that when training they often experience several problems, including not giving the material correctly, looking pale, having an unclear voice, and/or shaking hands. Basic level swimming trainer training to increase participants' knowledge and skills in swimming training at district or city level. This activity is a form of community service. It is hoped that after swimming coach training, participants will not only have knowledge and practice, but also have legal skills in leading and training novice swimmers.